Concern About the Association Between Sex and Birth Weight of Babies: A Cross-Sectional Randomized Finding From a Nigerian Hospital - Ahmadu, BU; Abubakar, IH; Halima, A; Ruqayya, A; Suleiman, GM (Journal of Nepal Paediatric Society, 2013)
Introduction: Sexual antagonism is seen particularly where maternally and paternally derived alleles battle over fetal growth, which may result in sex differences regarding birth weight of babies. We examined the association between sex and birth weight of babies in the University of Maiduguri Teaching Hospital. Materials and Methods: One hundred babies selected by systematic random sampling had their birth weights determined using bassinet weighing scale. Likelihood ratio chi-square test of association was used to investigate the relationship between sex and birth weight. Results: A total of 100 babies participated in this study. There were 53 (53.0 %) males and 47 (47.0 %) females giving a male to female ratio of 1.1:1. Majority of the babies 82 (82.0 %) had normal birth weight (2500 – 3900 g). The mean (SD) birth weight for male and female babies were 313 (62), 95 CI (296 – 330 g), and 290 (055), 95 CI (275 – 307 g) respectively. The overall mean (SD) birth weight of the babies was 302 (0.59), 95 CI (291 – 314 g). Association between birth weight and sex of the babies was found to be significant (χ2 = 9.317, p = 0.025). Conclusion: Birth weight was significantly associated with sex: males had higher birth weights than females. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7090 J Nepal Paediatr Soc. 2013;33(1):21-24.